The Influence Of Human Resources, Internal Control And Information Technology On The Timeliness Of Submitting Financial Reports At The Balangan Regency SKPD - Wulandari, Agustina; Novianty, Nadya; Analisa, Analisa; Yusri, Yusri (Jurnal Ekonomi, 2024)
Good government financial management is influenced by factors such as human resources, information technology, and internal control. This study aims to examine the impact of these factors on the timeliness of financial report submission in the Regional Work Units (SKPD) of Balangan Regency. The research was conducted in 32 SKPDs with a total population of 88 employees, all of whom were selected as respondents through total sampling. Data collection was carried out using questionnaires, and the data was analyzed through Multiple Linear Regression with SPSS 20, including tests for validity, reliability, F-tests, t-tests, and the coefficient of determination. The findings show that: (1) Human resources have a significant effect on financial reporting timeliness, with a sig. value of 0.001 < 0.05. (2) Internal control significantly affects timeliness, with a sig. value of 0.009 < 0.05. (3) Information technology also has a significant impact, with a sig. value of 0.025 < 0.05. In conclusion, human resources, internal control, and information technology all significantly influence the timeliness of financial report submissions in SKPDs in Balangan Regency.